2018
DOI: 10.3390/ijerph15091987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mining Activities on the Release of Heavy Metals (HMs) in a Typical Mountain Headwater Region, the Qinghai-Tibet Plateau in China

Abstract: Understanding the heavy metal (HM) contamination in alpine mountain headwaters regions is important to maintaining the ecosystem stability of the basin. A total of 119 water samples and 104 sediment samples were collected along tributaries and the main course of Heihe River. The concentrations of eight heavy metals (As, Cd, Cr, Cu, Mn, Ni, Pb, and Zn) in water and sediment were measured to describe their spatial variability and to assess water quality. To identify the origins and pathways of HMs, anions, catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 49 publications
0
20
1
1
Order By: Relevance
“…In addition to As, the concentration of other trace metals in this study are lower than the Chinese Environmental Quality Standards limit values. Previously, many studies have shown that the content of Cd and Hg in this region has been increasing rapidly in recent years [36,54], but the concentration of both elements in this study was still at a low level.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to As, the concentration of other trace metals in this study are lower than the Chinese Environmental Quality Standards limit values. Previously, many studies have shown that the content of Cd and Hg in this region has been increasing rapidly in recent years [36,54], but the concentration of both elements in this study was still at a low level.…”
Section: Discussioncontrasting
confidence: 56%
“…Baku mutu sedimen dengan standard sediment quality guideline values for metals and associated levels of concern to be used in Doing assesments of sediment quality (2003) Hasil Analisis Histopatologis Insang Ikan Nila Literatur tentang konsentrasi logam berat pada ikan nila yang dipelihara dalam keramba di kolam bekas tambang batubara yang ada di kawasan bekas tambang batubara masih jarang ditemukan. Menurut Wei et al (2018), logam berat (As, Cd, Cr, Cu, Mn, Ni, Pb, dan Zn) dalam air dan sedimen pada tersebut umumnya berasal dari aktivitas penambangan lokal.…”
Section: Hasil Logam Berat DI Badan Perairan Dan Ikanunclassified
“…In addition, some serpentine deposits have been extended into agricultural regions (Ye-Tao et al 2012;Neilson and Rajakaruna 2015), including in Mouriki-Thiva, Central Greece, where Antibachi et al (2012) found 621-2639 and 134-856 mg kg −1 of Ni and Cr in soil, respectively. Moreover, due to high rainfall and erosion, serpentine soil and sediments can separate from its main body, transport through irrigation systems, and deposit in valleys and lowlands which are used extensively for agriculture (Wei et al 2018). Ranau Valley in Malaysia was reported to have Mn (43,063.8 mg kg −1 ), Cr (7332.2 mg kg −1 ), Ni (6322.3 mg kg −1 ), and Co (1004.7 mg kg −1 ) in paddy soil due to erosion, transport, and sedimentation (Aziz et al 2015).…”
Section: Introductionmentioning
confidence: 99%